3D‐Printed Tissue Models: Engineering a Novel 3D Printed Vascularized Tissue Model for Investigating Breast Cancer Metastasis to Bone (Adv. Healthcare Mater. 15/2020). Issue 15 (5th August 2020) - Cui, Haitao; Esworthy, Timothy; Zhou, Xuan; Hann, Sung Yun; Glazer, Robert I.; Li, Rong; Zhang, Lijie Grace
Abstract : To better study cancer metastasis, in article number 1900924 by Lijie Grace Zhang and co‐workers, a 3D printed in vitro vascularized cancer model is created by integrating a tumor, an endothelialized vessel, and a nanobone tissue using various inks to demonstrate the multiple interactions between breast cancer cells and the vascularized bone environment. It is expected that the model will be notably valuable for future cancer research and new therapeutic discovery.